Construction of methodology for characterization of disruptive methods/technologies (Research, Society and Development, 2023)
The objective of the project was to develop a methodology for the characterization of disruptive methods/technologies. Therefore, in order to quantitatively judge the degree of disruptiveness of an application, a framework for evaluating disruptive innovations was developed based on the multidimensionality of identifying potential disruptiveness, which is based on characteristics such as the maturity of the project, its ability to of cost reductions, their market niches. Thus, in order to put these innovation indicators into practice and carry out a faster and more objective validation, a web technology platform was developed in a single-page application format called ShareTech, developed in JavaScript, with a robust profile. modern. From the results obtained, it is concluded that the methodology developed will have the potential to evaluate / characterize technologies with disruptive innovations, thus helping several institutions of science, technology and innovation, in the selection of which technologies can reach the market and which have greater possibility of public or private investment. After using the methodology and software to analyze the disruptiveness of technologies, there will be a better dimensioning and appreciation of research and science, technology and innovation institutions based in Brazil.